EVOLUTION OF SIDE SUPPORT FRN EVROPIAN INTEGRATION EFFORTS FOR UKRAINE - Гнилицька, Анастасія; Михайлюк, Олена (SWorldJournal, 2023)
In the article on the basis of officially available materials,normative documents,available statistical, interviews with authorized persons, mass media notification the author is trying to analizy the multi-vector direction of cooperation between Ukraine